2010
DOI: 10.2202/1934-2659.1467
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study and Modeling of Aerobic Biological Oxidation of Organic Wastewater

Abstract: The complex organic wastewater from agrochemical industry consists of a large number of solids and dissolved compounds. For the design and scale-up of any activated sludge reactor, it is desirable to know the kinetics of oxidation, which strongly depends upon the nature of wastewater and the microorganism. In the present work, the kinetics of aerobic biological oxidation of an agrochemical plant waste is investigated, having initial COD of 800-1200 mg/L. Experiments are performed at five different dissolved ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The previous experiments [16] showed that a DO level of 2.5 mg L À1 and an MLSS concentration of 9000 mg L À1 have resulted in the maximum COD reduction of 74.77% as shown in Table 3.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The previous experiments [16] showed that a DO level of 2.5 mg L À1 and an MLSS concentration of 9000 mg L À1 have resulted in the maximum COD reduction of 74.77% as shown in Table 3.…”
Section: Resultsmentioning
confidence: 84%
“…The oxygen transfer was sufficient by surface aeration and no air sparging was needed. Further, negligible foaming was observed [11,16,22,23]. Table 6 shows the effluent analysis indicating TN deficiency for aerobic suspended growth process, whereas the amount of TP was sufficient.…”
Section: High Levels Of Agitationmentioning
confidence: 96%
See 2 more Smart Citations
“…32 Several previous studies also demonstrated the evaluation of the kinetic coefficients for various wastewater treatments. 39,96,97 Kinetic coefficients for a wastewater treatment system at different VSS concentrations were determined in a study by Karkare et al 98 In research conducted by Naghizadeh et al, 99 the kinetic coefficient for the Monod equation was estimated in a submerged membrane reactor used to treat sewage. The measured values for k d , Ks, k and Y were 0.51 (day −1 ), 65.5 mg L −1 , 1.78 (day −1 ) and 0.6 mgVVS mgCOD −1 , respectively.…”
Section: Kinetics Of Substrate Removalmentioning
confidence: 99%